Placement method of flowable building materials

By using mineral particles colloidal dispersions with ≥7 pH as thickener in 3D printing technology, the problems of short initial solidification time of building materials and release of harmful substances are solved, high yield stress and stability are achieved, and hydraulic stiffness is expanded Application scope of cement.

CN119301086APending Publication Date: 2025-01-10HOLCIM TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380044388.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-09
Filing Date
2023-05-08
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

In existing 3D printing techniques, the short initial solidification time of building materials leads to an increased risk of material accumulation in mixing devices, pumps and printheads, and limits the choice of hydraulic binders, especially in the presence of sulfur-containing minerals. Hazardous substances, such as H2S gas.

Method used

Add mineral particles colloidal dispersions dispersed in liquids as thickeners to the building materials to ensure that the thickeners have a pH of ≥7 to avoid the formation of an acidic environment and by adding amorphous dioxide to the building materials Thickening agents such as silicon or layered silicates increase yield stress, prevent solid mineral particles from aggregating, enhance dispersion, and ensure that the material has sufficient yield strength before solidification.

Benefits of technology

Achieving significant increase in yield stress of building materials without changing the solidification process, ensuring that each material layer can withstand the weight of its own and subsequent layers without collapsing, expanding the range of hydraulic cement that can be used for 3D printing, including Sulfur composite cement avoids the release of harmful substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301086A_ABST
    Figure CN119301086A_ABST
Patent Text Reader

Abstract

A method of placing a flowable building material comprising hydraulic cement for layer-by-layer construction of a structural component, such as for 3D concrete printing, includes delivering the flowable building material to a deposition head, placing the building material through an outlet of the deposition head to form a layer of building material, and before placing the building material, placing the building material through the outlet of the deposition head to form the layer of building material. A thickening agent is added to the building material such that the placed material has an increased yield stress prior to the occurrence of solidification compared to the material in the conveying step, in which successive layers of building material are placed on top of each other, in which the thickening agent is added in the form of a colloidal dispersion of mineral particles dispersed in a liquid, the colloidal dispersion preferably has a pH of > = 7.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a method of placing a flowable building material comprising hydraulic cement for layer-by-layer construction of structures and building components, such as for 3D concrete or mortar printing.

[0002] 3D printing is a construction technology generally known as "additive manufacturing" and consists in joining materials to produce an object layer by layer from 3D model data or other electronic data sources. In particular, successive layers of material are formed by industrial robots under computer control. It has been proposed to develop 3D printers capable of producing structural buildings from building materials, which may be mortar or concrete. According to these proposals, the building material is extruded through a nozzle to build the structural component layer by layer without the use of formwork or any subsequent vibration. The possibility of building structures without formwork is a major advantage in terms of productivity, freedom of construction and cost reduction.

[0003] Typically, 3D printing of building materials is a continuous process that includes delivering new concrete, mortar or micromortar to a deposition head and placing building materials through the outlet of the deposition head to form concrete layers. While placing the concrete, mortar or micromortar, the deposition head moves under computer control to create layers of building materials according to the underlying 3D model. In particular, the deposition head places strips of new concrete or mortar material. In order to allow the new concrete or mortar to move smoothly through each part of the delivery process to the deposition head, the rheology of the new material must be consistent.

[0004] However, the building material must not only be fluid enough for conveying and extrusion, but also strong enough to provide the mechanical stability required for 3D printed structures before the hydraulic binder sets. In particular, the lower layer of the building material should withstand the loads applied by the upper layer without collapsing or deforming.

[0005] Therefore, flowable building materials suitable for 3D printing usually contain a large amount of hydraulic binders with a short initial setting time, such as aluminate cement. However, binders with a short initial setting time increase the risk of material accumulation in mixing devices, pumps and print heads.

[0006] Another aspect to consider is printing speed. High printing speeds are required to reduce building time and ensure adequate interlayer adhesion. In some cases, this is achieved by using hydraulic binders with a short initial setting time, as the deposited material hardens quickly and is able to support subsequently deposited layers.

[0007] 3D printed elements also require strong bonding strength between the deposited layers to ensure that the 3D printed structure has sufficient overall strength. For this purpose, it is advantageous to lay down a layer while the previous layer is still new. However, in the case of hydraulic binders with a short initial setting time, the operational flexibility is very limited.

[0008] From an operational flexibility perspective, it would be ideal to have a flowable building material with a long initial setting time, i.e., a constant consistency that does not increase too much over time, as this would allow more time to adjust the printing process, such as changing printing parameters during the building process.

[0009] In order to meet some of the above requirements, it has been proposed to add various admixtures to the flowable building material in the deposition head, immediately prior to depositing the material through the outlet of the deposition head. This allows the material properties to be optimized separately for the process of pumping the material to the deposition head and for the process of depositing the material layer by layer. In particular, the building material can be designed to have a low plastic viscosity and a low yield stress for good pumpability and adjusted by adding suitable admixtures in the deposition head to obtain the material properties required for the deposition process.

[0010] For example, WO 2017 / 221058 A1 discloses adding a rheology modifier to a flowable building material in a deposition head to increase the yield stress. Starch ethers, cellulose ethers, water-soluble polyacrylamides, casein and / or welan gum have been suggested as rheology modifiers.

[0011] However, the rheology modifiers used in the prior art have the disadvantage of causing an acidic environment when added to cement, which in some cases has the potential to produce the release of harmful substances. This is particularly true when the cement contains sulfur-containing minerals, such as ground granulated blast furnace slag or concrete demolition waste, where the acidic admixtures can lead to the formation of H2S gas. This limits the choice of hydraulic binders to cement types that contain little or no sulfur.

[0012] Therefore, the present invention aims to improve printable hydraulic building materials to overcome the above problems. In particular, the present invention aims to expand the range of cements that can be used as building materials in 3D printing applications, adding rheology modifiers to the building materials in the print head.

[0013] In order to overcome these deficiencies, the present invention provides, according to its first aspect, a method for placing a flowable building material comprising hydraulic cement for building a structural component layer by layer, such as for 3D concrete printing, the method comprising:

[0014] delivering the flowable building material to a deposition head,

[0015] placing the building material through the outlet of the deposition head to form a layer of building material,

[0016] adding a thickener to the building material prior to placing the building material so that the placed material has an increased yield stress before setting occurs compared to the material in the delivery step,

[0017] where successive layers of building materials are placed on top of each other,

[0018] The thickener is added in the form of a colloidal dispersion of mineral particles dispersed in a liquid, the colloidal dispersion preferably having a pH value of ≥7.

[0019] The invention is therefore based on the idea of ​​using a specific inorganic thickener in the form of a colloidal dispersion which, when in contact with the building material, does not form an acidic environment and thus prevents the release of harmful substances such as H2S. In this way, a wide range of hydraulic cements can be used for 3D printing, including sulfur-containing composite cements. By adding the colloidal dispersion to the building material, the yield strength of the building material extruded through the nozzle of the deposition head is increased, so that each building material layer is able to withstand its own weight and the weight of subsequent layers placed on top of each other without collapsing.

[0020] The addition of thickeners in the form of colloidal dispersions significantly prevents the aggregation of solid mineral particles and enhances their dispersibility in building materials.

[0021] Preferably, water is used as the dispersion medium for the colloidal dispersion.

[0022] The mineral particles preferably have a particle size distribution characterized by a D10 of ≥2nm, preferably ≥5nm and a D90 of ≤200nm, preferably ≤100nm. D10 refers to the 10th percentile of the particle size distribution (calculated by particle size volume), i.e. 10% of the volume is formed by particles with a size less than the D10 diameter. Similarly, D90 refers to the 90th percentile of the particle size distribution (calculated by particle size volume), i.e. 90% of the volume is formed by particles with a size less than the D90 diameter. The particle size distribution is measured by dynamic light scattering according to standard ISO-22412-2017. The values ​​are determined by volume and calculated from the particle size distribution (by volume) of the colloidal dispersion.

[0023] Preferably, the specific surface area of ​​the mineral particles is 100-500m 2 The specific surface area refers to the BET specific surface area measured according to standard ISO9277:2010.

[0024] The addition of a thickener according to the invention results in an increased yield stress characteristic being obtained almost immediately after placement, i.e. before setting occurs. The increase in yield stress achieved according to the invention is therefore independent of the setting process of the hydraulic binder of the building material. The invention is therefore generally carried out without controlling or accelerating the setting process.

[0025] As used herein, a thickener is understood to mean a viscosity modifying admixture as defined in European Standard EN-934-2 of August 2012, which is an admixture that limits segregation (i.e. the separation of concrete components according to their respective density and weight) in fresh concrete or mortar by improving adhesion.

[0026] The expression "before setting occurs" is understood to refer to the initial setting time defined in standard EN 196-3. According to the needle penetration test method disclosed in said standard, the start of the setting process ("initial setting") is determined when the concrete paste, due to its stiffness, exerts a predefined resistance to a test needle inserted into the paste. In particular, the initial setting time is the period between the time when water is added to the cement and the time when a 1 mm square section needle cannot penetrate the cement paste placed in a Vicat mould at a distance of 5 to 7 mm from the bottom of the mould.

[0027] Due to the yield strength increasing effect brought about by the thickener, the presence or addition of setting accelerators is preferably excluded. Setting accelerators are understood to mean admixtures added in order to shorten the initial setting time as defined in the European standard EN-934-2 of August 2012.

[0028] The building material may be a cement mortar or cement micromortar, ie a mixture of hydraulic cement, potentially additional mineral components such as ground limestone, water, sand and chemical admixtures.

[0029] The building material may also be concrete, ie a mixture of hydraulic cement, potentially additional mineral components such as ground limestone, water, sand, gravel and chemical admixtures.

[0030] In a preferred embodiment, the building material is a flowable ultra high performance concrete, i.e. a mixture of cement, fine limestone material, fine sand and / or sand, high range water reducing admixture, possible accelerating admixture and water, which produces a compressive strength of at least 100 MPa at 28 days.

[0031] The thickener may be added to the building material just before reaching the deposition head or in the deposition head.

[0032] Preferably, the thickener and the building material are mixed with one another before the building material is placed, wherein the mixing is preferably carried out using a static mixer.

[0033] Preferably, the thickener is added continuously to the flow of the conveyed building material to achieve a continuous process. Preferably, not only the addition of the thickener, but also the mixing of the thickener with the flow of the conveyed building material is performed continuously, so that a continuous deposition of the mixture of building material and thickener can be achieved while moving the deposition head according to the basic 3D data.

[0034] The amount of thickener added continuously to the flow of building material per time unit is preferably controlled in order to adjust a defined ratio of thickener to building material in the final mixture deposited layer by layer. In particular, the flow rate of the building material delivered to the deposition head is measured and the flow rate of the thickener added to the flow of building material is adjusted to achieve the defined ratio. Alternatively, a fixed flow rate of the building material delivered to the deposition head is adjusted and the flow rate of the thickener added to the flow of building material is selected to achieve the defined ratio.

[0035] Preferably, the step of placing the building material comprises extruding the building material in paste form through a nozzle of the deposition head.

[0036] As regards the colloidal dispersion, a preferred embodiment provides that the colloidal dispersion has a solid content of 20-55 wt.-%. The solid content is measured by drying the colloidal dispersion at 105° C. for 24 hours and measuring and calculating the weight loss before and after the drying phase. The solid content of the colloidal dispersion comprises or consists of the above-mentioned mineral particles. Preferably, the solid content of the colloidal dispersion does not contain any components other than the mineral particles which produce a thickening effect when added to the flowable building material.

[0037] As regards the nature of the mineral particles, a preferred embodiment provides that the thickener comprises at least one member selected from the group consisting of pozzolanic materials and phyllosilicates. Pozzolanic materials are siliceous and aluminous materials and preferably consist of or comprise amorphous silica or fumed alumina. For example, Sigma-Aldrich is available in The layered silicate may be a clay, such as a natural clay including sepiolite, attapulgite, bentonite, colloidite, hectorite, saponite, montmorillonite, kaolinite and wollastonite, or a synthetic clay such as the Silica® provided by Byk Additives Limited.

[0038] The amount of colloidal dispersion added to the flowable building material depends inter alia on the type of mineral particles, the desired yield strength development and the solids content of the dispersion. In particular, the higher the solids content of the colloidal dispersion, the less mass of thickener needs to be added to the building material.

[0039] According to a preferred embodiment, the thickener is amorphous silica and / or fumed alumina and is added to the building material in an amount of 8-18 g / l, preferably 10-12 g / l, the amount being defined as the weight of the solid content of the thickener per volume of the building material.

[0040] According to a preferred embodiment, the thickener is a layered silicate clay and is added to the building material in an amount of 2-5 g / l, the amount being defined as the weight of the solid content of the thickener per volume of the building material.

[0041] The amount of thickener added to the building material is preferably selected so that the layer of material placed has sufficient stability so that it does not collapse under its own weight or the weight of a subsequent layer placed on it. In this respect, a preferred mode of operation is that after the first layer of building material is placed, at least one subsequent layer of building material is placed on the first layer, wherein the amount of thickener added to the building material is selected to increase the yield stress so that the first layer does not collapse under the load of the at least one subsequent layer.

[0042] In this context, "no collapse" means that the height of the layer does not decrease by more than 10%, preferably by more than 5%, under the load of the at least one subsequent layer.

[0043] Since the method of the invention is intended to achieve a rapid building progress, the above stability criterion is preferably met at a minimum building speed, which is defined by the maximum time interval between the placement of two subsequent layers of material. According to a preferred mode of operation, before placing the building material of the subsequent layer on the building material of the first layer, the building material of the first layer is allowed to rest for a period not exceeding 2 minutes, preferably for a period of 30-60 seconds.

[0044] According to a preferred embodiment of the present invention, the yield stress of the newly placed building material measured 30-60 seconds after its placement is 500-2000Pa, preferably 400-1000Pa. Therefore, it is preferred to select the amount of thickener added to the building material to increase the yield stress to 500-2000Pa, preferably 400-1000Pa. The yield stress is measured with a scissors gauge. The scissors gauge includes a blade that is inserted into the material to be tested and applies an increasing torque to it. When damage occurs in the material, the blade begins to rotate, usually when the torque reaches its maximum value, which is considered to be a characteristic value representing the yield stress of the material. The yield stress measurement is preferably carried out within 30-60 seconds after the material is placed.

[0045] The conveying step of the method of the invention comprises conveying the building material in a flowable state to the deposition head. In particular, the conveying of the building material is carried out by pumping. Preferably, the material is conveyed in a wet state and can be deposited without adding any other components except the thickener.

[0046] Preferably, new building material, such as new concrete or new mortar, is stored in silos or any other storage container, or in a mixer in a ready-mix delivery truck, and is delivered directly from the storage site to the deposition head.

[0047] Preferably, during the delivery step, ie before the thickener is added, the building material is designed to have self-leveling properties. In particular, the yield stress of the material to be delivered is between 200 and 400 Pa when measured with a scissor gauge.

[0048] In order to achieve the above-mentioned transportability or pumpability, a water reducing agent, in particular a plasticizer or superplasticizer, preferably a plasticizer based on polyoxypolycarboxylate or phosphonate, is preferably added to the building material before the transport step. Preferably, the flowable building material comprises both a superplasticizer based on phosphonate and a superplasticizer based on polycarboxylate.

[0049] Water reducers make it possible to reduce the amount of mixing water for a given processability by generally 10-15%. As examples of water reducers, mention may be made of lignin sulfonates, hydroxycarboxylic acids, carbohydrates and other specific organic compounds, such as glycerol, polyvinyl alcohol, sodium aluminum methyl silicate and p-aminobenzenesulfonic acid, as described in Concrete Admixtures Handbook, Properties Science and Technology, VS Ramachandran, Noyes Publications, 1984.

[0050] Superplasticizers belong to a new class of water reducers and are capable of reducing the water content of the mixing water by about 30% by mass at a given processability. As examples of superplasticizers, PCP superplasticizers may be noted. The term "PCP" or "polyoxypolycarboxylate" is to be understood according to the invention as copolymers of acrylic acid or methacrylic acid and their polyoxyethylene (POE) esters.

[0051] Good results have been obtained with the following types of superplasticizers: Sika's Viscocrete 510-P (based on polycarboxylate), Chryso's Optima 100 (based on modified phosphonate) and Sika's Viscocrete Tempo 533 (based on polycarboxylate).

[0052] Preferably, the building material comprises 4-15 kg, more preferably 8-12 kg of water reducer, plasticizer or superplasticizer per cubic meter of flowable building material. If more than one type of water reducer, plasticizer or superplasticizer is used, the amount of 5-15 kg, preferably 8-12 kg, refers to the total amount of all such ingredients per cubic meter of flowable building material.

[0053] The flowable building material contains hydraulic cement, which is a hydraulic binder containing at least 50 wt.-% of CaO and SiO2, which sets due to a chemical hydration reaction between dry ingredients and water. In addition to CaO and SiO2, the hydraulic cement may also contain other components. Various mineral additives, such as silica fume, granulated blast furnace slag (GBFs), fly ash, natural pozzolan, calcined clay, ground limestone or concrete demolition waste can be added to Portland cement to obtain Portland composite cement. The mineral additive, usually between 10 and 50 wt.-% of the total weight of the hydraulic cement, is ground granulated blast furnace slag, fly ash, pozzolan, ground limestone or a mixture thereof in most applications. The addition of silica fume is particularly beneficial for the production of high-strength 3D printing mortar or concrete (i.e., having a compressive strength of at least 70 MPa at 28 days).

[0054] Preferably, the hydraulic cement consists of Portland cement mixed with any of the mineral additives described in the cement standard EN 197-1 of April 2012.

[0055] Preferably, the hydraulic cement comprises at least 30 wt.-% Portland clinker.

[0056] Preferably, the hydraulic cement comprises at least 10 wt.-% of supplementary cementitious material, preferably selected from ground granulated blast furnace slag and concrete demolition waste. When the hydraulic cement comprises at least 10 wt.-% of blast furnace slag, the use of acidic admixtures and thickeners having a pH of less than 7 leads to the formation of harmful substances, such as H2S gas formed by the dissolution of sulfur-containing minerals in the binder (such as slag and concrete demolition waste). The thickener added to the building material preferably has a pH of at least 7, which prevents the formation of harmful substances when the two components are mixed together.

[0057] Suitable cements are those described in the European standard NF EN 197-1 of April 2012, or mixtures thereof, preferably cements of the CEM I, CEM II, CEM III, CEM IV or CEM V type.

[0058] Hydraulic cement can also be fine cement or ultrafine cement, i.e., hydraulic cement ground to a finer fineness than standard hydraulic cement. For example, the fineness can be higher than 5000 cm 2 / g, and reaches up to 13000cm 2 / g or even 15000cm 2 / g value (expressed in terms of cement Blaine fineness).

[0059] According to a preferred embodiment, the flowable building material does not contain any aluminate cement, such as calcium aluminate cement. Alternatively, aluminate cement, such as calcium aluminate cement or calcium sulfoaluminate cement, may be present in an amount of <5 wt%, preferably <2.0 wt%, based on the total amount of hydraulic cement.

[0060] According to a preferred embodiment, the hydraulic cement comprises Portland cement and aluminate cement, wherein the aluminate cement is present in an amount of <5% by weight, preferably <2% by weight, based on the total amount of hydraulic cement.

[0061] Calcium aluminate cement is a cement consisting mainly of hydraulic calcium aluminate. Other names are "aluminous cement", "high alumina cement" and in French "Ciment fondu". Calcium aluminate cement has a short initial setting time and is therefore considered less preferred. Hydraulic cements with a short initial setting time increase the risk of material accumulation in the deposition head. In addition, a short initial setting time may reduce the bond strength between layers placed on top of one another, since the previous layer may no longer be fresh when the subsequent layer is placed. Limiting the content of calcium aluminate cement is also preferred in terms of cost, since calcium aluminate cement is relatively expensive.

[0062] In addition, the flowable building material may contain a mineral filler, such as limestone. Adding a fine fraction of a mineral filler is particularly beneficial for producing a high-strength 3D printing mortar or concrete. Preferably, the mineral filler, such as limestone, has a particle size of <50 μm, preferably <40 μm. More preferably, the mineral filler, such as limestone, comprises a fine fraction having a particle size distribution characterized by a D50 of 3-5 μm and a D90 of 8-12 μm and a coarse fraction having a particle size distribution characterized by a D50 of 10-12 μm and a D90 of 35-40 μm.

[0063] Furthermore, the aggregate present in the flowable building material may comprise micro sand with a particle size <1 mm, a second sand with a particle size <4 mm and optional aggregate (>4 mm and <32 mm).

[0064] The flowable building material may contain metal fibers and / or organic fibers and / or glass fibers. The volume amount of the fibers is typically 0.5 to 8% relative to the total volume of the new concrete composition. The amount of metal fibers expressed by volume of the final hardened concrete is typically less than 3%, for example from 0.5 to 2.5%, preferably about 2%. The amount of organic fibers expressed on the same basis is typically 1 to 8%, preferably 2 to 5%. The metal fibers are typically selected from steel fibers, such as high-strength steel fibers, amorphous steel fibers or stainless steel fibers. The steel fibers may optionally be coated with non-ferrous metals, such as copper, zinc, nickel (or their alloys).

[0065] The individual length (l) of the metal fibers is generally at least 2 mm and preferably 10-30 mm. The ratio l / d (d being the diameter of the fiber) is generally 10 to 300, preferably 30 to 300, preferably 30 to 100.

[0066] Organic fibers include polyvinyl alcohol (PVA) fibers, polyacrylonitrile (PAN) fibers, polyethylene (PE) fibers, high-density polyethylene (HDPE) fibers, polypropylene (PP) fibers, homopolymer or copolymer fibers, polyamide or polyimide fibers. Mixtures of these fibers can be used. The organic reinforcing fibers used in the present invention can be divided into the following categories: high modulus active fibers, low modulus inactive fibers and low modulus active fibers. The presence of organic fibers makes it possible to change the concrete behavior associated with heat or fire.

[0067] The individual length of the organic fibers is preferably 5 to 40 mm, preferably 6 to 12 mm. The organic fibers are preferably PVA fibers.

[0068] The effective water / cement ratio (wt / wt ratio) of the building material used in the present invention is preferably 0.4 to 0.6, more preferably 0.48 to 0.57. The effective water / binder ratio may vary, for example, due to the water required when using mineral additives. The water / binder ratio is defined as the mass ratio of the amount of water to the dry mass of hydraulic cement (Portland cement and mineral additives).

[0069] According to a second aspect, the present invention relates to a kit of parts for building a structural component layer by layer, for example for 3D concrete printing, in particular for carrying out the method of the first aspect of the invention, comprising:

[0070] - flowable building materials comprising hydraulic cement,

[0071] - a thickener for increasing the yield stress of the flowable building material before setting occurs, said thickener being in the form of a colloidal dispersion of mineral particles dispersed in a liquid, said colloidal dispersion preferably having a pH value of ≥7.

[0072] The present invention will now be explained with reference to the following examples.

[0073] In the examples, the following mortar compositions were used.

[0074]

[0075]

[0076] In addition, the following thickeners were used:

[0077] Thickener #1:

[0078] Name: Laponite SL-25

[0079] Chemical composition: synthetic clay (layered silicate)

[0080] Supplier: BYK

[0081] Solid content: 25 wt.-%

[0082] pH: 9.4

[0083] Thickener #2:

[0084] Name: Ludox SM-30

[0085] Chemical composition: Amorphous nano-silicon dioxide

[0086] Supplier: Grace

[0087] Solid content: 30 wt.-%

[0088] Comments: Single peak, very small particle size (<10 nm), sodium counterion, surface area: 320-400 m 2 / g

[0089] pH: 9.7-10.3

[0090] Thickener #3:

[0091] Name: Ludox HS-40

[0092] Chemical composition: Amorphous nano-silicon dioxide

[0093] Supplier: Grace

[0094] Solid content: 40 wt.-%

[0095] Notes: Single peak, small particle size (about 10 nm), sodium counterion, surface area: 220 m 2 / g pH: 9.2-9.9

[0096] The mortar composition was prepared by performing the following steps:

[0097] step detail Duration Dry powder mixing PV(140±5rpm) 1 minute Water introduction PV(140±5rpm) <30 seconds mix PV(140±5rpm) 2 minutes mix GV(285±10rpm) 3 minutes Thickener addition <10 seconds mix PV(140±5rpm) 30 seconds

[0098] Embodiment 1:

[0099] Mortar #1 was mixed with thickener #1 at different dosages of thickener: 7 g / l, 10 g / l and 12.5 g / l. Figure 1 The initial yield stress just after placement of the mix strip is shown. Figure 2 The development of the yield stress over time is shown.

[0100] The results show that higher dosage rates of thickener lead to higher yield stresses. A dosage rate of 7 g / l shows insufficient yield stress. A dosage rate of 12.5 g / l leads to an initial yield stress that is too large. A dosage rate of 10 g / l provides a good compromise.

[0101] Embodiment 2:

[0102] Mortar #3 was mixed with thickener #1 at different dosages of thickener: 10 g / l, 15 g / l and 30 g / l. Figure 3 The initial yield stress just after placement of the mix strip is shown. Figure 4 The development of the yield stress over time is shown.

[0103] Likewise, the results show that higher dosage rates of thickener lead to higher yield stresses. A dosage rate of 10 g / l shows insufficient yield stress. A dosage rate of 30 g / l leads to an initial yield stress that is too large. A dosage rate of 15 g / l provides a good compromise.

[0104] Embodiment 3:

[0105] Mortar #2 was mixed with either thickener #2 or #3 at different dosages of thickener: 20 g / l, 27.5 g / l and 35 g / l for thickener #3 and 27.5 g / l and 35 g / l for thickener #2. Figure 5 shows the initial yield stress just after placement of the tape containing thickener #2, and Figure 6 The initial yield stress is shown just after placement of the mix tape containing thickener #3. Figure 7 The development of the yield stress over time is shown.

[0106] Adequate initial yield stress was observed for a dosage rate of 27.5 g / l for Thickener #3 and 35 g / l for Thickener #2. Figure 7 It is shown that an appropriate yield stress accumulation rate is achieved when either of the two thickeners is used.

Claims

1. A method of placing a flowable building material comprising hydraulic cement for layer-by-layer construction of structures and building components, such as for 3D concrete printing, the method comprising: delivering the flowable building material to a deposition head, placing the building material through the outlet of the deposition head to form a layer of building material, adding a thickener to the building material prior to placing the building material so that the placed material has an increased yield stress before setting occurs compared to the material in the delivery step, where successive layers of building materials are placed on top of each other, The thickener is added in the form of a colloidal dispersion of mineral particles dispersed in a liquid, the colloidal dispersion preferably having a pH value of ≥7.

2. The method according to claim 1, wherein water is used as the dispersion medium of the colloidal dispersion.

3. The method according to claim 1 or 2, wherein the mineral particles have a particle size distribution characterized by a D10 of ≥2 nm, preferably ≥5 nm, and a D90 of ≤200 nm, preferably ≤100 nm.

4. A method according to claim 1, 2 or 3, wherein the mineral particles have a particle size of 100-500 m / s measured according to standard ISO 9277:2010. 2 / g BET specific surface area.

5. The process according to any one of claims 1 to 4, wherein the colloidal dispersion has a solids content of 20 to 55 wt.-%.

6. The method according to any one of claims 1 to 5, wherein the thickener comprises at least one member selected from the group consisting of pozzolanic materials and layered silicates.

7. The method of any one of claims 1 to 6, wherein the thickener comprises at least one member selected from the group consisting of amorphous silica, fumed alumina, and layered silicate clay.

8. A method according to any one of claims 1 to 7, wherein the step of placing the building material comprises extruding the building material in a paste form through a nozzle of the deposition head.

9. The method according to any one of claims 1 to 8, wherein after placing a first layer of building material, at least one subsequent layer of building material is placed on the first layer, wherein the amount of thickener added to the building material is selected to increase the yield stress so that the first layer does not collapse under the load of the at least one subsequent layer.

10. A method according to any one of claims 1 to 9, wherein the yield stress of the newly placed building material measured 30 to 60 seconds after its placement is 500 to 2000 Pa, preferably 400 to 1000 Pa.

11. The method according to any one of claims 1 to 10, wherein the building material is concrete, cement mortar or cement micromortar.

12. The method according to any one of claims 1 to 11, wherein the thickener is amorphous silica and / or fumed alumina and is added to the building material in an amount of 8 to 18 g / l, preferably 10 to 12 g / l, the amount being defined as the weight of the solid content of the thickener per volume of building material.

13. The method according to any one of claims 1 to 11, wherein the thickener is a layered silicate clay and is added to the building material in an amount of 2 to 5 g / l, the amount being defined as the weight of the solid content of the thickener per volume of the building material.

14. The method according to any one of claims 1 to 13, wherein the hydraulic cement comprises at least 30 wt.-% Portland clinker.

15. The method according to any one of claims 1 to 14, wherein the hydraulic cement comprises at least 10 wt.-% of supplementary cementitious material, preferably selected from ground granulated blast furnace slag and concrete demolition waste.

16. The method according to any one of claims 1 to 15, wherein before the conveying step, a water reducing agent, in particular a plasticizer or a superplasticizer, preferably a plasticizer based on polyoxypolycarboxylates or phosphonates, is added to the building material, wherein the conveying of the building material is carried out by pumping.

17. A kit of parts for building structural parts layer by layer, for example for 3D concrete printing, in particular for carrying out the method according to any one of claims 1 to 16, comprising: - flowable building materials comprising hydraulic cement, - a thickener for increasing the yield stress of the flowable building material before setting occurs, said thickener being in the form of a colloidal dispersion of mineral particles dispersed in a liquid, said colloidal dispersion preferably having a pH value of ≥7.

Citation Information

Patent Citations

  • Online control of rheology of building material for 3D printing

    WO2017221058A1